Three-point MEMS heat flux sensor for turbulent heat transfer measurement in internal combustion engines. (September 2019) - Dejima, Kazuhito; Nakabeppu, Osamu; Nakamura, Yuto; Tsuchiya, Tomohiro; Nagasaka, Keisuke
A heat flux sensor was developed with micro-electro-mechanical systems (MEMS) technologies for investigating turbulent heat transfer characteristics in engines. The sensor has three thin-film resistance temperature detectors (RTDs) of a square 315 µm on a side on a 900 µm diameter circle in rotational symmetry. The performances of the MEMS systems sensor were tested in an open combustion chamber and a laboratory engine. In the open chamber tests, it was revealed that the MEMS sensor can measure the wall heat fluxes reflecting flow states of gas phase. In addition, the noise was evaluated as 3.8 kW/m 2 with the standard deviation against the wall heat flux of a few hundred kW/m 2 . From these results, it was proved that the MEMS sensor has the potential to observe turbulent heat transfer on the order over 10 kW/m 2 in the engine. In the laboratory engine test, the wall heat flux for continuous 200 cycles was measured with a good signal-to-noise ratio. The noise was evaluated as 13.4 kW/m 2 with the standard deviation despite the noisy environment. Furthermore, it was proved that the MEMS sensor has the comparable scale with the turbulence in the engine because the three adjacent detectors measured similar but different phase oscillations in the local instantaneous heat fluxes. In addition, a heat flux vector reflecting the state of the local instantaneous heat transfer was visualized by the adjacent three-point measurement. It is expected that the three-point MEMS sensor will be a useful tool for the engine heat transfer research.